2005
DOI: 10.1111/j.1365-2966.2005.09330.x
|View full text |Cite
|
Sign up to set email alerts
|

The INT Photometric H  Survey of the Northern Galactic Plane (IPHAS)

Abstract: The Isaac Newton Telescope (INT) Photometric Hα Survey of the Northern Galactic Plane (IPHAS) is a 1800‐deg2 CCD survey of the northern Milky Way spanning the latitude range −5° < b < + 5° and reaching down to r′≃ 20 (10σ). Representative observations and an assessment of point‐source data from IPHAS, now underway, are presented. The data obtained are Wide Field Camera images in the Hα narrow‐band, and Sloan r′ and i′ broad‐band filters. We simulate IPHAS (r′−Hα, r′−i′) point‐source colours using a spectrophot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
506
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 476 publications
(517 citation statements)
references
References 37 publications
9
506
0
1
Order By: Relevance
“…The INT/WFC Photometric Hα Survey of the northern Galactic Plane (IPHAS; Drew et al 2005) is the first comprehensive digital survey of the northern Galactic disc (|b| 5 • ), covering a Galactic longitude range of 30 • l 215 • . Imaging is performed in the r, i and Hα bands down to r ∼ 20.…”
Section: Introductionmentioning
confidence: 99%
“…The INT/WFC Photometric Hα Survey of the northern Galactic Plane (IPHAS; Drew et al 2005) is the first comprehensive digital survey of the northern Galactic disc (|b| 5 • ), covering a Galactic longitude range of 30 • l 215 • . Imaging is performed in the r, i and Hα bands down to r ∼ 20.…”
Section: Introductionmentioning
confidence: 99%
“…VPHAS+ and its twin surveys in the Northern hemisphere (IPHAS, and UVEX; Drew et al 2005;Groot et al 2009) are ideal tools for the successful identification of the missing population of faint stellar remnants of low-to intermediate-mass stars in the Galactic plane. Optical follow-up spectroscopy, with moderate resolution and S/N >20, is sufficient to confirm the white dwarfs and to measure their atmospheric parameters, but higher quality data are necessary if more accurate spectroscopic parallaxes are to be sought.…”
Section: S U M M a Ry A N D C O N C L U S I O N Smentioning
confidence: 99%
“…Pipeline data reduction and data distribution are handled by the Cambridge Astronomical Survey Unit. The main product of the survey is its point sources photometric catalogue, whose presented by Drew et al (2005), and can also be found in the IPHAS home web page at http://www.iphas.org.…”
Section: Iphas Overviewmentioning
confidence: 99%